A practical approach to estimate the degree of binder activity of reclaimed asphalt materials. Issue 5 (4th May 2021) - Menegusso Pires, Gustavo; Lo Presti, Davide; Airey, Gordon Dan
Abstract : Using Reclaimed Asphalt (RA) in new asphalt mixtures can reduce the amount of new material required thereby saving money and natural resources. In addition, asphalt mixtures with RA have shown comparable properties and performance to that generally associated with asphalt mixtures made with 100% virgin material. However, RA content in pavement surface layers is still limited due to specification and technical limitations. For higher contents, the aged RA binder must be analysed to accurately determine the requirements for virgin binders and additives while the degree of blending (DOB) between the RA binder and the virgin binder also needs to be quantified. This is not a simple process and generally designers assume one of two opposing theories associated with 100% (full blending) or 0% ("Black Rock") DOB. This paper proposes a new approach to estimate a unique property of the RA known as the Degree of Binder Activity (DoA) as a function of the processing temperatures of the RA. The study showed positive results and indicated that this DoA approach can be used as a tool to better understand RA in order to improve the binder/blend design for recycled asphalt mixtures.